Guidelines on themanagement of arterial hypertension and related comorbidities in Latin America (2017)
ABI, ankle-brachial index; ABPM, ambulatory blood pressure monitoring; ACCORD, Action to Control Cardiovascular Risk in Diabetes; ACE-I, angiotensin-converting-enzyme-inhibitors; ARB, AT1 blockers; BP, blood pressure; CARMELA, Cardiovascular Risk Factor Multiple Evaluation in Latin America; CARMEN, Community Actions for Multifactorial Reduction of Non- Communicable Diseases; CCB, calcium channel blocker; CCM, Wagner’s Chronic Care Model; CDC, Chronic Disease Center; CTA, computed tomography angiography; CV, cardiovascular; DALY, disability-adjusted life year; DPP- 4, dipeptidyl-peptidase-4; GLP-1, glucagon-like peptide 1; HBPM, home blood pressure monitoring; HOPE, Heart Outcomes Prevention Evaluation; HOT, Hypertension Optimal Treatment; HT, hypertension; LA, Latin America; LASH, Latin American Society of Hypertension; MRA, magnetic resonance angiography; NCD, noncommunicable disease; OSAS, obstructive apnea–hypopnea syndrome; PAD, peripheral artery disease; PAHO, Pan American Health Organization; RAAS, renin–angiotensin–aldosterone system; RISS, Redes Integradas de Servicios de Salud; SGLUT2, sodium–glucose cotransporter-2; SPRINT, SBP Intervention Trial; UKPDS, United Kingdom Prospective Diabetes Study; VIDA, Veracruz Initiative for Diabetes Awareness